2021
DOI: 10.1007/s10578-021-01231-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Bullying Victimization and Perpetration and Non-suicidal Self-injury: A Systematic Review

Abstract: Experience of bullying may be a significant risk factor for non-suicidal self-injury (NSSI). This study had three aims: to systematically investigate the association between bullying and NSSI, analyze the possible mechanisms underlying the two phenomena, and evaluate any differences between bullying victimization and bullying perpetration with respect to NSSI. A systematic search about the association between bullying victimization and perpetration and NSSI was conducted using specific databases (PubMed, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
4
30
0
1
Order By: Relevance
“…In the current study, the prevalence of caregiver-reported bullying victimization was 15.3%, which is lower than the 22.4% of children aged 6–11 reported in the National Survey of Children’s Health ( Lebrun-Harris et al, 2020 ). Consistent with previous studies ( Serafini et al, 2021 ), the prevalence of any NSSI or suicidality was higher among those being bullied (18.2%) compared to their non-bullied peers (7.4%). While the prevalence of these behaviors within the non-bullied group is similar to earlier studies ( DeVille et al, 2020 ; Janiri et al, 2020 ), a higher prevalence in the bullied group suggests that bullying may be an important and potentially preventable risk factor for NSSI and suicidality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the prevalence of caregiver-reported bullying victimization was 15.3%, which is lower than the 22.4% of children aged 6–11 reported in the National Survey of Children’s Health ( Lebrun-Harris et al, 2020 ). Consistent with previous studies ( Serafini et al, 2021 ), the prevalence of any NSSI or suicidality was higher among those being bullied (18.2%) compared to their non-bullied peers (7.4%). While the prevalence of these behaviors within the non-bullied group is similar to earlier studies ( DeVille et al, 2020 ; Janiri et al, 2020 ), a higher prevalence in the bullied group suggests that bullying may be an important and potentially preventable risk factor for NSSI and suicidality.…”
Section: Discussionsupporting
confidence: 91%
“…Suicide was the second leading cause of death for children aged 10–14 years in 2019 in the US ( CDC, 2020b ) and rates continue to rise substantially ( National Center for Health Statistics, 2019 ). Bullying victimization was identified as a modifiable risk factor for suicide attempts in adolescence ( Kim et al, 2011 ) or adulthood ( Meltzer et al, 2011 ), but associations of bullying with self-harm behavior and thoughts in younger children are not well-described ( Serafini et al, 2021 ). One study showed that both non-suicidal self-injury (NSSI; e.g., superficial cutting) and suicidality (e.g., passive and active suicidal ideation, intent, and/or behavior) were more prevalent in adults who suffered childhood bullying ( Copeland et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data related to bullying, peer socialisation, and time use of devices were similar in the pre-COVID and COVID samples. As we know from the literature, there was a strong association between being a victim of bullying and psychosocial functioning impairment, as well as physical and psychopathological symptoms [ 32 34 ]. Similarly, the association between excessive internet use (more than three hours per day), already increased in the pre-COVID era [ 35 , 36 ], and internalising mental health problems (specifically anxiety, depression, and mixed mental disorders) is well known [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Despite the differences across different types of bullying perpetration/peer victimisation, few studies have investigated the impact of types on their clinical characteristics. 9 Specifically, previous research has already pointed out that bullying perpetration/peer victimisation could impose significant risks for SI, NSSI, and SA, [21][22][23][24][25] while whether the relationship between bullying perpetration/peer victimisation and suicidality/NSSI varies from different bullying types (i.e., overt, relational, reputational) remains unexplored.…”
Section: Introductionmentioning
confidence: 99%